Accessing Contexts and Approaches for Entrepreneurship: The Impact of COVID-19 on Brazil’s Entrepreneurial Environment - Moreira Silva, João Paulo; Sztando, Andrzej (Identyfikując konteksty i podejścia do przedsiębiorczości: wpływ COVID-19 na środowisko przedsiębiorczości w Brazylii, 2023)
During the early days of the field of entrepreneurship research, entrepreneurial activity was taken as a sequenced process, derived from planning, and carried out by individuals with innate capabilities. Since the rise of newly emerging approaches to entrepreneurship, such as effectuation and bricolage, the entrepreneurial process has come to be perceived differently. This article aims to introduce and discuss the contextual aspects of entrepreneurship, prioritising this paradigmatic shift. A survey with data on the entrepreneurial environment in Brazil, an emerging economy with a complex and tumultuous economic context, was conducted. It was observed that the COVID-19 pandemic has accentuated difficulties already encountered in access to resources by Brazilian entrepreneurs, as well as catapulted the registration of need-based ventures. The article provides new insights to the discussion regarding the need to understand entrepreneurship as a contextual phenomenon.
Ekonomia XXI Wieku = Economics of the 21st Century, 2023, Nr 26, s. 5-16
Keywords: entrepreneurship; contextual aspects of entrepreneurship; Brazil; effectuation; bricolage; przedsiębiorczość; kontekstowe aspekty przedsiębiorczości; Brazylia; efektuacja